South African social theory : Steve Biko - Esterhuizen, Charlton (Department of Sociology, 2016)
The complexity and dynamism of society provides the sociologist with interesting challenges. The methods and instruments we use to study and understand society have to evolve with the same dynamism. This minor dissertation investigates sociological theory in South Africa. The primary aim of this dissertation is to determine if one can produce or derive sociological theory from the work of black South Africans, specifically Steve Biko. To this end one has to disseminate the idea of sociological theory and consider how it is constructed. It is also important to highlight the contextual and progressive nature of theory. To illustrate this, I briefly outline the development of sociology as an academic discipline. In addition I consider the implications of macro and micro theory, paying particular attention to Marxism and Weberianism. This is exemplary in terms of showing the contextual relevance and the progressive thinking which inform social theory. It is widely acknowledged that Comte, Marx, Durkheim and Weber were the founding fathers of sociology. I consider the contributions of Ntsikana, Tiyo Soga, Anton Lembede, Pixley Seme and finally Steve Biko as a means of demonstrating the potential local intellectual to inform a new social theory The nature of this research dictated the use of a qualitative research design. The review of literature and biographical accounts were used to construct the lineage of South African intellectuals. The key intellectual considered in this paper is Steve Biko. The source of the data was his salient work: "I Write What I Like". Thematic analysis was used to analyse the relevant texts, mainly the Miles Huberman approach. This allowed me to identify the key analytical constructs of Steve Biko's work. These analytical constructs would be the foundation of a possible sociological theory.